A complete guide to reptiles of Australia - Wilson, Steve K. 1954-; Swan, Gerry (New Holland, 2013)
A Complete Guide to Reptiles, now in its fourth, revised edition, features more than 940 species of reptiles named in Australia. The text and maps have been updated and newly described species are included.Species are grouped in families, for example Skinks, Dragons Monitors, Blind Snakes and Pythons. Species are illustrated with lively colour photographs showing them in their natural habitat
Includes bibliographical references and index
Keywords: Reptiles / Australia / Identification; Australien